East Nusa Tenggara (NTT) Student Communication Accommodation Strategy in Sidoarjo - Sahrul Ali Sandi; Ferry Adhi Dharma (Universitas Muhammadiyah Sidoarjo, 2023)
This qualitative study aims to explore the accommodation strategies employed by students from East Nusa Tenggara (NTT) studying in Sidoarjo, Indonesia, in their interactions with local students and the surrounding community. Drawing on the communication accommodation theory, data was collected through purposive sampling using interviews, observations, and documentation. The findings revealed three forms of communication accommodation: convergence (using both Indonesian and Javanese languages during interactions), divergence (using their native language from NTT), and overaccommodation (expressed through loud laughter and speech patterns). The study highlights the significance of the accommodation process between NTT students and local students and community members in achieving effective cross-cultural communication. The implications of these findings shed light on the importance of cultural sensitivity and understanding in fostering harmonious interactions among diverse populations. Highlights: The study explores cross-cultural accommodation strategies of NTT students in Sidoarjo. Findings reveal convergence, divergence, and overaccommodation as forms of communication accommodation. The study emphasizes the importance of cultural sensitivity for effective cross-cultural communication. Keywords: cross-cultural accommodation, NTT students, communication accommodation, cultural sensitivity, effective communication